A methodology to investigate financial challenges and strategic responses of Net Zero Building in Malaysia - Mohd Taharill, Nur Ameera Batrisyia; Ayob, Mohd Fairullazi (2025)
Net Zero Buildings (NZBs) have become a crucial element in supporting Malaysia’s commitment towards achieving environmental sustainability and carbon neutrality. To achieve this imperative goal, the buildings in Malaysia have been demanded to design with a balanced energy consumption and renewable energy generation for providing zero net carbon emissions throughout the entire service life. Despite the noteworthy environmental and economic benefits of NZB, its present implementation in the Malaysian construction industry is still limited due to significant challenges particularly in terms of financial feasibility and sustainability in operating and maintaining the NZB buildings over the life span. This video is prepared with the objective to present a methodology proposed for the study to investigate financial challenges and strategic responses in the implementation of NZBs practice in Malaysia. A qualitative research strategy is proposed as methodology for the study, embedding a comprehensive literature review with interview approach to interview people that have established knowledge, skills or experience in the green building projects. The study will be focusing on identifying the quality of available data used as inputs in the estimation of initial and future costs of NZB building and evaluating the effectiveness of current financial incentives provided to foster the NZB implementation in the Malaysian construction industry. The study is expected to highlight major barriers that hinder the NZB implementation and include with the appropriate strategies for recommendation to enhance the financial viability and adoption of NZB implementation in Malaysia. The study findings could serve as a valuable reference to stakeholders and policymakers in helping them to improve the economic framework in the NZB implementation roadmap to be in line with Malaysia's sustainable development goals and National Energy Transition Roadmap (NETR).